2021
DOI: 10.1111/acem.14396
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐versus landmark‐guided medium‐sized joint arthrocentesis: A randomized clinical trial

Abstract: Objectives: Arthrocentesis is commonly performed in the emergency department, but success rates vary based on location. Presently, there is a paucity of data assessing the utility of ultrasound-guided (USG) medium-sized joint arthrocentesis. The objective of this study was to compare the success of USG and landmark-guided (LMG) medium-sized joint arthrocentesis. Methods:This was a single-center, prospective, randomized clinical trial (NCT03327584) of a convenience sample of adult patients who presented to an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…While the risks of an arthrocentesis include pain, bleeding, and infection, ultrasound guidance has been proven to minimize these risks, enhancing patient satisfaction and patient outcomes [ 6 ]. As a result, joint aspirations using ultrasound guidance are safer, more effective, and faster than using the landmark technique alone [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the risks of an arthrocentesis include pain, bleeding, and infection, ultrasound guidance has been proven to minimize these risks, enhancing patient satisfaction and patient outcomes [ 6 ]. As a result, joint aspirations using ultrasound guidance are safer, more effective, and faster than using the landmark technique alone [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2,7,[10][11][12][13] A retrospective review of 101 POCUS examinations by Acuna et al 7 showed that POCUS use for arthrocentesis was successful in 92.1% of cases when performed by emergency medicine residents. Gibbons et al 14 showed that ultrasound-guided aspiration of medium joints (elbow, wrist, ankle) in 44 adult ED patients had a 94% success rate compared with 60% success in landmark-guided aspiration. Finally, a study by Thom et al 13 showed that POCUS of the hip joint performed by emergency physicians led to expedited diagnosis (68 vs 208 minutes) and arthrocentesis (211 vs 602 minutes) in septic arthritis cases compared with radiology-performed studies.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…While routine interventions targeting peripheral joints or periarticular structures can be performed using anatomical landmarks, in case of a challenging procedure, imaging guidance is preferable. 44 While fluoroscopy is a valid alternative, ultrasound is the preferred modality for guiding interventions due to the absence of ionising radiation and better visualisation of soft tissue structures. 45 46 Recommendation 10: showing and explaining imaging findings of CiAs to people with such conditions may help them understand their condition and improve treatment adherence in gout.…”
Section: Recommendation 3: When Characteristic Features Of Msu Crysta...mentioning
confidence: 99%